Making London Porcelain—A Multidisciplinary Project Connecting Local Communities with the Technological and Innovation Histories of London’s Early Porcelain Manufacturers - Lucia Burgio; Kelly Domoney; Georgia Haseldine; Caroline McCaffrey-Howarth (Heritage, 2023)
This collaborative multidisciplinary pilot project involving the Victoria and Albert Museum (V&A), the Ashmolean Museum, and Newham Borough of London, examined the composition of a selection of eighteenth-century porcelain objects by two of London’s first porcelain manufacturers, Bow and Chelsea. As the first science-based public engagement project to be piloted by the V&A, it succeeded in bringing together young Londoners and their communities to investigate local histories of scientific and artistic innovation through the analysis and remaking of eighteenth-century porcelain. Scientific object analysis informed activities with local sixth-form students, revealing the intimate link between art and science, and showcasing the V&A Science Lab as a national hub for heritage science. Public outreach activities, including an exhibition at Stratford Library and workshops for Newham Heritage Month also provided hands-on learning, including curatorial and object-handling experience, and the embodied practices of remaking. Ultimately, this project stimulated new ways of engaging with ceramics collections and explored how the creativity and ingenuity of eighteenth-century ceramics pioneers can provide inspiration for the next generation of makers.